Incremental value of Veterans Specific Activity Questionnaire and the YMCA-step test for the assessment of cardiorespiratory fitness in population-based studies. (29th August 2020) - Teren, Andrej; Zachariae, Silke; Beutner, Frank; Ubrich, Romy; Sandri, Marcus; Engel, Christoph; Löffler, Markus; Gielen, Stephan
Abstract: Background: Cardiorespiratory fitness is a well-established independent predictor of cardiovascular health. However, the relevance of alternative exercise and non-exercise tests for cardiorespiratory fitness assessment in large cohorts has not been studied in detail. We aimed to evaluate the YMCA-step test and the Veterans Specific Activity Questionnaire (VSAQ) for the estimation of cardiorespiratory fitness in the general population. Methods: One hundred and five subjects answered the VSAQ, performed the YMCA-step test and a maximal cardiopulmonary exercise test (CPX) and gave BORG ratings for both exercise tests (BORGSTEP, BORGCPX ). Correlations of peak oxygen uptake on a treadmill (VO2_PEAK ) with VSAQ, BORGSTEP, one-minute, post-exercise heartbeat count, and peak oxygen uptake during the step test (VO2_STEP ) were determined. Moreover, the incremental values of the questionnaire and the step test in addition to other fitness-related parameters were evaluated using block-wise hierarchical regression analysis. Results: Eighty-six subjects completed the step test according to the protocol. For completers, correlations of VO2_PEAK with the age- and gender-adjusted VSAQ, heartbeat count and VO2_STEP were 0.67, 0.63 and 0.49, respectively. However, using hierarchical regression analysis, age, gender and body mass index already explained 68.8% of the variance of VO2_PEAK, while the additional benefit of VSAQ was rather low (3.4%). The inclusion of BORGSTEP, heartbeat count and VO2_STEP increased R 2 by a further 2.2%, 3.3% and 5.6%, respectively, yielding a total R 2 of 83.3%. Conclusions: Neither VSAQ nor the YMCA-step test contributes sufficiently to the assessment of cardiorespiratory fitness in population-based studies.